DrosoPhyla: Resources for Drosophilid Phylogeny and Systematics. (3rd August 2021) - Finet, Cédric; Kassner, Victoria A; Carvalho, Antonio B; Chung, Henry; Day, Jonathan P; Day, Stephanie; Delaney, Emily K; De Ré, Francine C; Dufour, Héloïse D; Dupim, Eduardo; Izumitani, Hiroyuki F; Gautério, Thaísa B; et al.
Abstract: The vinegar fly Drosophila melanogaster is a pivotal model for invertebrate development, genetics, physiology, neuroscience, and disease. The whole family Drosophilidae, which contains over 4, 400 species, offers a plethora of cases for comparative and evolutionary studies. Despite a long history of phylogenetic inference, many relationships remain unresolved among the genera, subgenera, and species groups in the Drosophilidae. To clarify these relationships, we first developed a set of new genomic markers and assembled a multilocus data set of 17 genes from 704 species of Drosophilidae. We then inferred a species tree with highly supported groups for this family. Additionally, we were able to determine the phylogenetic position of some previously unplaced species. These results establish a new framework for investigating the evolution of traits in fruit flies, as well as valuable resources for systematics.